Pengaruh model project citizen terhadap hasil belajar Pendidikan Pancasila siswa SMP - B.syaripatun Nisa; Edy Herianto; Sawaludin Sawaludin (Journal of Education, Cultural and Politics, 2026)
This study aims to determine the effect of implementing the Project Citizen learning model on the learning outcomes of eighth-grade students at SMPN 1 Wanasaba in the subject of Pancasila Education. This research was motivated by students low learning outcomes and their limited active participation in the learning process. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of 203 students, with a sample of 30 students. Data were collected through pre-test and post-test instruments that had been tested for validity and reliability. Data analysis included tests of normality, homogeneity, and hypothesis testing using an independent samples t-test with the assistance of SPSS. The results showed a significance value of 0.001 < 0.05, indicating that the alternative hypothesis was accepted. Thus, the Project Citizen learning model has a significant effect on improving students learning outcomes and can serve as an effective alternative learning approach.